Footprints of past geological events in rocks from Krucze Skały excavation (Karkonosze Mountains, SW Poland) - Michalak, Joanna (Bulletin of Geography. Physical Geography Series, 2019)
Krucze Skały excavation is located within Izera-Kowary Unit, which is a subdivision of Karkonosze-Izera Massif. Traces of numerous geological events were recognized and described before in other locations from this unit. In this specific location only pegmatitic intrusions were tested until now. This research considers geological history recorded in petrography and mineralogy of all remaining rocks. Samples collected along the excavation were analyzed using polarising microscope and XRD method. During the examination records of magmatic genesis of these rocks protolith as a S-type granite were found as well as evidences of MP-LT and LP-HT metamorphism, metasomathosis and hydrothermal activity. In some cases it is arguable which processes and in what point of geological history created certain features of rocks.